Empoderamiento familiar y apoyo docente, en el proceso de enseñanza de un estudiante con autismo - Oviedo Chuchuca, Charlie Jonathan; Ramirez Freire, Jereley Salome (Machala : Universidad Técnica de Machala, 2022)
Autism is a neurodevelopmental disorder that is characterized by repetitive or rigid language, little ability for non-verbal communication, specific interests, visual and auditory hypersensitivity, these characteristics affect the correct development of the child in the school, social and family. Students with autism have specific needs, which must be met to achieve a correct development in the teaching-learning process, therefore the family and the teacher must act through joint work. With respect to the categories of research analysis, the following problem arises, what is the relationship between family empowerment and teacher support in the teaching process of a student with autism? Therefore, this case study aims to determine the relationship between family empowerment and teacher support in the teaching process of a 14-year-old student, diagnosed with autism, from a regular institution in the city of Machala, El Oro province Regarding the methodology for the execution of this research, a descriptive case study was used, assuming a qualitative approach, therefore information collection instruments were applied, among them, interviews directed to the family and teacher, and the scale of positive parenting. The purpose of these instruments was to collect information in the family and educational context, for its subsequent analysis and preparation of the appropriate conclusions and recommendations. In conclusion, after the analysis of the information, it has been verified that there is a correlation between the study variables, however in the first years of schooling of the minor, there were discrepancies on the part of the family and the teacher due to the lack of information, difference of ideas and little communication, in front of the needs of the student, which obstructed the teaching process. On the other hand, the teaching work against the needs of the student and the family are not adequate, and the teaching process within the classroom is developed through uncreative strategies. In addition, the family is not provided with information about the minor's condition, which exposes the teacher's ignorance of the subject, however, within this case study, the student with ASD has a progression and functionality in their daily activities which has allowed him to improve his personal growth, thanks to the early intervention provided by his family.
El autismo es un trastorno del neurodesarrollo que se caracteriza por presentar un lenguaje repetitivo o rígido, poca habilidad para la comunicación no verbal, intereses específicos, hipersensibilidad visual y auditiva, estas características afectan al correcto desenvolvimiento del niño en el ámbito, escolar, social y familiar. Los estudiantes con autismo tienen necesidades específicas, que deben ser atendidas para lograr un correcto desenvolvimiento en el proceso de enseñanza aprendizaje, por ello la familia y el docente deben actuar mediante un trabajo en conjunto. Con respecto a las categorías de análisis de la investigación se plantea la siguiente problemática, ¿ Qué relación existe entre el empoderamiento familiar y el apoyo docente en el proceso de enseñanza de un estudiante con autismo? Por ende, el presente estudio de caso tiene como objetivo, determinar la relación entre el empoderamiento familiar y el apoyo docente en el proceso de enseñanza de un estudiante de 14 años, diagnosticado con autismo, de institución regular de la ciudad de Machala, provincia del Oro.
Keywords: AUTISMO; EMPODERAMIENTO FAMILIAR; APOYO DOCENTE